1996
DOI: 10.1080/02705060.1996.9663491
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Food Habits to Yellow Perch Growth and Population Structure in South Dakota Lakes

Abstract: We compared summer yellow perch (Perca flavescens) food habits among a wide range of perch population types in six South Dakota lakes. Chironomlds were a major dietary component in all populations with mean relative importance (RI) values ranging from 29 to 55. Corixids were a major diety component for highquality (large proprtion of fish 2200 mm TL) yellow perch populations, with mean RI values ranging from 22 to 26. Zooplankters were important sources of prey for yellow perch in low-quality (low proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…Yellow perch shift their diet as they grow (Lott et al 1996;Sherwood et al 2000). Juvenile yellow perch feed on large zooplankton, whereas older fish increase their reliance on benthic invertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yellow perch shift their diet as they grow (Lott et al 1996;Sherwood et al 2000). Juvenile yellow perch feed on large zooplankton, whereas older fish increase their reliance on benthic invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Yellow perch are ubiquitous across northeastern North America, and are found in freshwater ecosystems ranging in size from the St. Lawrence River and Great Lakes to small streams, rivers, and lakes. As it grows from a small schooling forage fish to a predator that can reach 500 g or more in larger water bodies, yellow perch feed successively on zooplankton, benthic invertebrates, and small fish (Lott et al 1996). Because yellow perch have a high tolerance to metals, they are often the only fish species present in highly metal-contaminated lakes (Couture and Rajotte 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Predicted lengths from the 13 populations used in the predicted length-at-age comparisons were used for this analysis. Predicted lengths-at-age-3 were used because this age group is commonly used for yellow perch growth assessments (Lott et al 1996(Lott et al , 1998Isermann et al 2007). SSD (the difference between female and male predicted lengths-at-age-3) was regressed against several variables including productivity of the lake [Trophic State Index based on total phosphorus (TSI TP , Carlson 1977)], lake morphometry (surface area in ha, maximum depth in m, and mean depth in m), and yellow perch gender-combined population dynamics: growth (K), maximum predicted length (L 1 ), total annual mortality (A), and recruitment variability (recruitment coefficient of determination, RCD).…”
Section: Methodsmentioning
confidence: 99%
“…Lott et al (1996) studied yellow perch populations in different types of South Dakota natural lakes. They found that yellow perch recruitment was more consistent in deep natural lakes with high shoreline development that contained submerged aquatic macrophytes than in shallow natural lakes with low shol-eline development and little or no aquatic vegetation.…”
Section: Introductionmentioning
confidence: 99%